Nebulised liposomal amphotericin-B as maintenance therapy in allergic bronchopulmonary aspergillosis: a randomised, multicentre trial. Issue 6 (16th June 2022) - Godet, Cendrine; Couturaud, Francis; Marchand-Adam, Sylvain; Pison, Christophe; Gagnadoux, Frédéric; Blanchard, Elodie; Taillé, Camille; Philippe, Bruno; Hirschi, Sandrine; Andréjak, Claire; Bourdin, Arnaud; Chenivesse, Cécile; et al.
Background: In allergic bronchopulmonary aspergillosis (ABPA), prolonged nebulised antifungal treatment may be a strategy for maintaining remission. Methods: We performed a randomised, single-blind, clinical trial in 30 centres. Patients with controlled ABPA after 4-month attack treatment (corticosteroids and itraconazole) were randomly assigned to nebulised liposomal amphotericin-B or placebo for 6 months. The primary outcome was occurrence of a first severe clinical exacerbation within 24 months following randomisation. Secondary outcomes included the median time to first severe clinical exacerbation, number of severe clinical exacerbations per patient, ABPA-related biological parameters. Results: Among 174 enrolled patients with ABPA from March 2015 through July 2017, 139 were controlled after 4-month attack treatment and were randomised. The primary outcome occurred in 33 (50.8%) out of 65 patients in the nebulised liposomal amphotericin-B group and 38 (51.3%) out of 74 in the placebo group (absolute difference −0.6%, 95% CI −16.8– +15.6%; OR 0.98, 95% CI 0.50–1.90; p=0.95). The median (interquartile range) time to first severe clinical exacerbation was longer in the liposomal amphotericin-B group: 337 days (168–476 days) versus 177 days (64–288 days). At the end of maintenance therapy, total immunoglobulin-E and Aspergillus precipitins were significantly decreased in the nebulised liposomal amphotericin-B group. Conclusions: In ABPA, maintenance therapy using nebulised liposomal amphotericin-B did not reduce the risk of severe clinical exacerbation. The presence of some positive secondary outcomes creates clinical equipoise for further research. In ABPA, maintenance therapy with nebulised liposomal amphotericin-B did not reduce the risk of severe exacerbation. There were differences favouring maintenance therapy in some secondary outcomes including delayed exacerbation and biological improvement. https://bit.ly/3CEaQD2